Considerations for vertical jump testing in collegiate basketball players: The impact of immediate individual versus social comparison feedback and team leaderboard engagement - Philipp, N. M.; Nijem, R. M.; Blackburn, S. D.; Cabarkapa, D.; Scott, C.; Fry, A. C. (International Journal of Sports Science & Coaching, 2024)
Recent literature has shown that the provision of feedback can enhance vertical jump performance acutely, as well as chronically when implemented during phases of training. The aim of our study was to investigate the influence of two types of visual feedback on performance and variability of countermovement jump-derived force-time characteristics in a cohort of male and female National Collegiate Athletic Association Division 1 basketball players. Specifically, individual visual feedback (IVF) was compared to a form of social comparison feedback (SCF), and authors hypothesized there to be performance increases and more stable measures in the SCF condition. In line with this hypothesis, findings suggested significantly enhanced performance in the SCF condition for seven out of eight force-time metrics (e.g. jump height and reactive strength index modified). However, given the small between-condition effect sizes, differences between conditions may lack practical significance. Furthermore, findings suggested less between-jump variability in the SCF condition, compared to the IVF condition, making for a more stable assessment. This in particular makes for more reliable measures, for which when studied over time, more subtle changes in performance may be observed. In summary, our findings highlight acutely enhanced vertical jump performance, and more stable measures, when athletes are exposed to an SCF condition, compared to a normal IVF condition. Practitioners are encouraged to consider these findings when planning vertical jump assessments and are discouraged from implementing different types of feedback at random, especially when measuring performance over time.